Witam :) dam 50 pkt za łatwe zadanie z matmy ! oto one ;P :
są to wyrazenia algebraiczne :D

1. Doprowadź do najprostszej postaci.

a) 6 (y-2) (y+2) + (3y -2)² - 4 (y-1)²


b) 2(2a+b)² - (2b+a)² + (a-2b)²

c) (4x-y)² + (2y-3x)² - (5x-y) (5x+y)


50 pkt czkae

3

Odpowiedzi

2009-12-08T15:00:54+01:00

1. Doprowadź do najprostszej postaci.

a) 6 (y-2) (y+2) + (3y -2)² - 4 (y-1)²=
=6y²-24+9y²12y+4-4y²+8y-4=
=11y²+20y-24


b) 2(2a+b)² - (2b+a)² + (a-2b)²=
=8a²+8ab+2b²-4b²+4ab-a²+a²-4ab+4b²=
=8a²+8ab+2b²

c) (4x-y)² + (2y-3x)² - (5x-y) (5x+y) =
=16x²-8xy+y²+4y²-12xy+9x²-25x²+y²=
=25x²-20xy+6y²
2009-12-08T15:04:45+01:00
A. 6 (y² + 2y - 2y -4) + 9y +4 - 4y² +1=
6y² + 12y - 12y -24 + 9y +4 - 4y² +1=
2y² +9y -19

b. 2(2a+b)² - (2b+a)² + (a-2b)²
2*(4a²+b²) - (4b²+a²) + (a² + 4b²)=
8a²+ 2b² - 4b²+a²+a² +4b²=
10a² +2b²

c. (4x-y)² + (2y-3x)² - (5x-y) (5x+y) =
16x² + y² + 4y² +9x² - 25x² + 5xy -5xy -y²=
4y²

Pozdro

  • fhm
  • Początkujący
2009-12-08T15:56:41+01:00
A) 6 (y-2) (y+2) + (3y -2)² - 4 (y-1)² = (6y - 12) (y+2) + 9y² - 4 - 4y² - 4 = 6y² - 12y - 12y - 24 + 9y² - 4 - 4y² - 4 = 11y² - 24y - 32

b) 2(2a+b)² - (2b+a)² + (a-2b)² = 8a² + 2b² - 4b² - a² + a² - 4b² = 8a² - 6b²

c) (4x-y)² + (2y-3x)² - (5x-y) (5x+y) = 16x² - y² + 4y² - 9x² - 25x² + 5xy - 5xy - y² = -5x² + 2y²